Web-Based Implementation of E-Marketing to Support Product Marketing of Chemical Manufacturing Company - Riswan Efendi Tarigan; Kartika Sari Dewi (Bina Nusantara University, 2015)
Currently, many company’s marketing strategies are limited only to face-to-face communication, telephone, facsimile, company portfolio, and product brochures. However, those marketing strategies are well- known to have limited impacts. Therefore, the presence of e-marketing as one of the marketing strategies would be appropriate to cover the weaknesses and to solve a number of the marketing problems. The purpose of this study is to discuss matters related to marketing, such as, proposing a marketing plan using website, expanding marketing segment, and introducing existing products for a chemical manufacturing company. The adopted research method is a descriptive method where the study is directly performed on the research object to acquire necessary data. The collected data are further analyzed using the Porter’s Five Force and SWOT analysis. Fi- nally, the work provides a number of recommendations for implementing e-marketing strategies to support the company business.